Do Male and Female Students Learn Differently? - Jamiah Jamiah; Murni Mahmud; Maemuna Muhayyang (ELT Worldwide: Journal of English Language Teaching, 2015)
This paper points out the gender differences in English learning.It investigated students’ language learning strategies as affected by gender differences. The data collected in 2015 from 15 male students and 15 female students’ of second grade at SMA Negeri 11 Makassar. It is to reveal their differences in English learning and the effect of gender differences in choosing language learning strategies. It is indicated that the entire student used six language learning strategies namely memory strategy, cognitive strategy, compensation strategy, metacognitive strateg, affective strategy and social strategy but they had different ways in using them. Mostly, females used social strategy because they were more emphatic, social thinking  and  like  cooperating with  their peers while  the  males  refered  to  the compensation startegy because their characteristics were more confident, fun, logical, active in expressing their opinion. So, it was concluded that gender differences affect in choosing language learning strategies of male and female students at SMA Negeri 11 Makassar.Keywords: language learning strategy, gender differences, classroom interaction